The use of a physiologically-based extraction test to assess relationships between bioaccessible metals in urban soil and neurodevelopmental conditions in children. (May 2016) - Hong, Jie; Wang, Yinding; McDermott, Suzanne; Cai, Bo; Aelion, C. Marjorie; Lead, Jamie
Abstract: Intellectual disability (ID) and cerebral palsy (CP) are serious neurodevelopment conditions and low birth weight (LBW) is correlated with both ID and CP. The actual causes and mechanisms for each of these child outcomes are not well understood. In this study, the relationship between bioaccessible metal concentrations in urban soil and these child conditions were investigated. A physiologically based extraction test (PBET) mimicking gastric and intestinal processes was applied to measure the bio-accessibility of four metals (cadmium (Cd), chromium (Cr), nickel (Ni), and lead (Pb)) in urban soil, and a Bayesian Kriging method was used to estimate metal concentrations in geocoded maternal residential sites. The results showed that bioaccessible metal concentrations of Cd, Ni, and Pb in the intestinal phase were statistically significantly associated with the child outcomes. Lead and nickel were associated with ID, lead and cadmium was associated with LBW, and cadmium was associated with CP. The total concentrations and stomach concentrations were not correlated to significant effects in any of the analyses. For lead, an estimated threshold value was found that was statistically significant in predicting low birth weight. The change point test was statistically significant (p value = 0.045) at an intestine threshold level of 9.2 mg/kg (95% confidence interval 8.9–9.4, p value = 0.0016), which corresponds to 130.6 mg/kg of total Pb concentration in the soil. This is a narrow confidence interval for an important relationship. Graphical abstract: Highlights: Correlation between bioavailable metals and child development were investigated. Cd, Ni, and Pb in the intestinal phase significantly affect neurodevelopment. Pb has a threshold value 130.6 mg/kg (of whole soil) for low birth weight. Abstract : Based on physiologically based extraction test, the 130.6 mg/kg of total Pb concentration in the soil may cause low birth weight of baby.